Designing a Competency Model for Administrative Managers in the Education Department of East Azerbaijan Province - Khayyati, Mehdi; haghkhah, Davoud; Danesh Shakib, Masoumeh (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The objective of this study is to identify the key components of competency for administrative managers at various levels within the Ministry of Education to propose a model. Methodology: To develop the research framework, the dimensions of the competency concept in the Education Department of East Azerbaijan Province were first extracted through document reviews, archival studies, and library research using card-based note-taking methods. Subsequently, the Delphi method was implemented in three stages, utilizing the insights of 29 experts familiar with the research topic to identify the most critical dimensions of competency within the Education Department of East Azerbaijan Province. A snowball sampling method was employed during this phase. In the next stage, after determining the sample size based on the Morgan table and applying simple random sampling, 218 administrative managers and staff (including experts and higher levels) from the Education Department of East Azerbaijan Province (encompassing one general department and five districts) were selected. Identified dimensions and factors were distributed to participants in the form of a questionnaire. Data were analyzed using structural equation modeling (SEM). Findings: Finally, a competency model for administrative managers in the Education Department of East Azerbaijan Province was designed, comprising 27 critical competencies categorized into four domains: operational competencies, social competencies, cognitive competencies, and meta-competencies. The only difference lies in the varying degrees of importance of these competencies for senior, mid-level, and junior administrative managers. Conclusion: The final proposed model can be utilized within the competency-based human resource management system of the Ministry of Education for training, recruitment, and performance evaluation of administrative managers at different levels.